Requirements to Professional Qualification and Education in the Modern Labor Market - Ghazaryan, Tigran (Bulletin of Yerevan University G: Economics, 2013)
In the article the main requirements of employers on professional education in contemporary conditions are considered. On the basis of existing explanations on interactions of employers with establishments of professional education in economic literature, the main requirements of contemporary employers to workers are outlined. Those requirements are the follows: education level, experience, sense of duty, initiative. With the help of analysis of statistical data on education and labor market in the Republic of Armenia, the problem is considered from the point of view of education and revenues to work.